2013
DOI: 10.1007/s10802-012-9693-9
|View full text |Cite
|
Sign up to set email alerts
|

Response Inhibition and ADHD Traits: Correlates and Heritability in a Community Sample

Abstract: Endophenotypes or intermediate phenotypes are of great interest in neuropsychiatric genetics because of their potential for facilitating gene discovery. We evaluated response inhibition, latency and variability measures derived from the stop task as endophenotypes of ADHD by testing whether they were related to ADHD traits in the general population, heritable and shared genetic risk with ADHD traits. Participants were 16,099 children and adolescents, ages 6 to 18 years who visited a local science center. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(221 citation statements)
references
References 43 publications
15
199
6
1
Order By: Relevance
“…In particular, we investigated individual differences in the SSRT (77). This measure of impulse control is known to show developmental increases across adolescence (78), and with impulse control disorders, such as ADHD (79,80), pathological gambling (81), and substance dependence (82). Importantly, some investigators argue that there is common neurocognitive component that underlies SSRT, delay discounting, and other measures of impulse control (83)(84)(85).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we investigated individual differences in the SSRT (77). This measure of impulse control is known to show developmental increases across adolescence (78), and with impulse control disorders, such as ADHD (79,80), pathological gambling (81), and substance dependence (82). Importantly, some investigators argue that there is common neurocognitive component that underlies SSRT, delay discounting, and other measures of impulse control (83)(84)(85).…”
Section: Methodsmentioning
confidence: 99%
“…Improved resolution will provide greater individual subject delineation of these networks and more precisely formulated testable hypotheses. For example, a large community sample of siblings revealed that motor inhibition on the stop task is coheritable with dimensional ratings of ADHD [19]. Determining the heritability of the structural and functional connectivity of the right IFC and anterior insula in the HCP sample would set the stage for future studies of affected probands and siblings in ADHD.…”
Section: Current Clues To the Neurobiology Of Adhdmentioning
confidence: 99%
“…As for ADHD, the idea is that, e.g., behavioral manifestations of the disorder such as impulsivity and hyperactivity are largely driven by difficulties in EFs such as attentional control (i.e., "paying attention and staying on task"; Nigg 2006), response inhibition (i.e., "the ability to stop a previously prepared response"; Nigg 2006) and working memory (i.e., "maintaining the amount of information online and to activate some information over other" ;Nigg 2006). Indeed, deficits in several EFs have been identified in individuals with ADHD, and, at this point in time, research continues to affirm cognitive deficits involved in the etiology of ADHD (Burgess et al 2010;Crosbie et al 2013;Kofler et al 2010;Sarver et al 2015;Tillman et al 2011). Perhaps predictably, emerging empirical studies concerned with investigations of the cooccurrence of ADHD and ADs have been mainly directed at the assessment of EFs in these comorbid populations.…”
Section: Introductionmentioning
confidence: 99%